2019
DOI: 10.1002/jwmg.21672
|View full text |Cite
|
Sign up to set email alerts
|

Survival and cause‐specific mortality of moose calves in Northeastern Minnesota

Abstract: Ungulate reproductive success (calf production and survival) influences population performance. The moose (Alces alces) population in northeastern Minnesota, USA, has declined 65% from 2006 to 2018 but has begun to stabilize. Because causes of this decline were largely unknown, we investigated production, survival, and cause‐specific mortality of calves of the global positioning system (GPS)‐collared females in this population. In 2013 and 2014, we GPS‐collared 74 neonates and monitored them for survival. In 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…Adult female moose use a variety of cover types for calving, often in proportion to their availability (Addison et al , Bowyer et al , Poole et al , McLaren et al ), yet some studies have reported selection for specific cover types used in post‐parturition areas, such as lowland conifer, shrublands, and regenerating forest (McGraw et al , McLaren et al ). Recently (2013–2015) in northeastern Minnesota, USA, few calf mortalities were observed at calving sites (Severud et al ), similar to observations elsewhere (Bubenik ). Moose and elk ( Cervus canadensis ) may use anthropogenic features as shields against predators, calving near roads or campsites that predators often avoid (Edwards , Lehman et al ).…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Adult female moose use a variety of cover types for calving, often in proportion to their availability (Addison et al , Bowyer et al , Poole et al , McLaren et al ), yet some studies have reported selection for specific cover types used in post‐parturition areas, such as lowland conifer, shrublands, and regenerating forest (McGraw et al , McLaren et al ). Recently (2013–2015) in northeastern Minnesota, USA, few calf mortalities were observed at calving sites (Severud et al ), similar to observations elsewhere (Bubenik ). Moose and elk ( Cervus canadensis ) may use anthropogenic features as shields against predators, calving near roads or campsites that predators often avoid (Edwards , Lehman et al ).…”
supporting
confidence: 79%
“…Median age of calves at capture was 2 days (range = 1–5 days). We monitored 155 females (50 in 2013, 56 in 2014, and 49 in 2015) and 139 calves (49 collared in 2013 and 25 collared in 2014, approximately 65 uncollared calves were remotely monitored in 2015 via their mother's movements; Severud et al ). Details of moose capture and collar specifics were described elsewhere (Butler et al ; Carstensen et al , ; Severud et al ; Obermoller et al ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations